35=-5(2y+5)

Rewrite the equation as -5(2y+5)=35.

-5(2y+5)=35

Divide each term in -5(2y+5)=35 by -5.

-5(2y+5)-5=35-5

Cancel the common factor of -5.

Cancel the common factor.

-5(2y+5)-5=35-5

Divide 2y+5 by 1.

2y+5=35-5

2y+5=35-5

Divide 35 by -5.

2y+5=-7

2y+5=-7

Subtract 5 from both sides of the equation.

2y=-7-5

Subtract 5 from -7.

2y=-12

2y=-12

Divide each term in 2y=-12 by 2.

2y2=-122

Cancel the common factor of 2.

Cancel the common factor.

2y2=-122

Divide y by 1.

y=-122

y=-122

Divide -12 by 2.

y=-6

y=-6

Solve for y 35=-5(2y+5)